The use of the Personal Pronoun "I" to Project Authorial Identities in Argumentative Essays (2020)
Academic authorial identity, manifested in the use of personal pronouns, has been discussed by many authors. Some authors claim that it is better if writers avoid using personal pronouns in writings, and some professors teach this thought, while some others support that it is better to write with own voice and that identity is always there. This thesis analyzes a corpus of argumentative essays written by students from Universidad de Los Andes for the TOEFL iBT to discover their use of the personal pronoun "I" and its incidence. The main objective was to find the distribution of the personal pronoun in three subcorpora organized according to three test performance levels: good, fair, and limited, and to find the identities that students projected in each level using the pronoun. Based on a model of taxonomy adapted from Tang and John (1999) it was discovered that the most used roles to project identity by the students were opinion holder and recounter of life's experiences, this situation could happen because of the kind of texts and question asked by the test. Here, the most surprising finding was that students classified in low levels use more the personal pronoun than their counterparts classified in high levels.